Insufficient knowledge of breast cancer risk factors among Malaysian female university students - Abu Samah, Asnarulkhadi; Ahmadian, Maryam; Abd Latiff, Latiffah (Canadian Center of Science and Education, 2016)
Background: Despite continuous argument about the efficacy of breast self-examination; it still could be a life-saving technique through inspiring and empowering women to take better control over their body/breast and health. This study investigated Malaysian female university students’ knowledge about breast cancer risk factors, signs, and symptoms and assessed breast self-examination frequency among students. Method: A cross-sectional survey was conducted in 2013 in nine public and private universities in the Klang Valley and Selangor. 842 female students were respondents for the self-administered survey technique. Simple descriptive and inferential statistics were employed for data analysis. Results: The uptake of breast self-examination (BSE) was less than 50% among the students. Most of students had insufficient knowledge on several breast cancer risk factors.